Exploiting voting strategies in partially replicated IEC 61499 applications - Mário de Sousa (2015)
In a modern industrial environment control programs are distributed among several devices. This raises new issues and challenges especially in failure modes. Building fault tolerant applications can be the solution in order a failure of one sub-component not to jeopardize the execution of the whole application. The authors have proposed a framework to support replicated IEC 61499 applications. In this paper we augment this framework with the support for different voting strategies, propose an extension of the replication communication protocol, and analyse the resulting fault-tolerance semantics. A limited implementation of the framework is also described.